Systematic Literature Review Filsafat Terhadap Ilmu Pengetahuan - Sucheri, Dian (Journal of Innovation in Teaching and Instructional Media, 2025)
This article reviews the criticism of science in the context of the philosophy of idealism and its impact on student character building. Through a Systematic Literature Review (SLR) approach, this research explores the contributions of prominent thinkers such as Karl R. Popper and Thomas Kuhn, who emphasized the importance of criticism in the development of scientific theories. SLR enables the identification and synthesis of relevant research, providing a comprehensive overview of the development of critique in the philosophy of science. The research shows that critique serves as an evaluative mechanism that encourages innovation and adaptation of science to new realities. The article also identifies gaps in existing research and recommends new directions for future studies, hoping to strengthen understanding of the role of critique in science as well as its application in student character education. Thus, the results of this study are expected to make a significant contribution to the development of educational theory and practice.